Group Counseling About Coping Stress Strategy in Special Needs Teachers - Susanto, Vania; Hartini, Nurul (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
The characteristics of children with special needs, which are unique and different from children in general, are certainly a challenge for teachers of children with special needs in providing education and assistance at school. This research aims to introduce stress coping strategies that can be a solution in overcoming the pressure faced by teachers who work with children with special needs through group counseling. The research participants in this study were teachers of children with special needs at School XX Surabaya. This research is a quasi-experimental one-group pretest-posttest design research that uses paired sample t-test analysis techniques to measure differences in stress levels before and after the group intervention is given. Based on the results of statistical analysis, it is known that there is a significant reduction in stress levels from the heavy to light and moderate categories, with a value of sig. (2-tailed) of 0.008 (<0.05). The qualitative research results also showed that the three participants obtained a therapeutic effect from group counseling which was carried out through a process of reflection, involvement in expressing emotions, identifying problems, giving feedback, finding insights from the discussion and interaction process, getting validation and being heard, as well as forming a perspective and new behaviors that are more constructive and adaptive in dealing with stress. So, it can be concluded that group counseling related to coping stress strategies is able to reduce stress levels in teachers who handle children with special needs at School XX Surabaya.Karakteristik anak berkebutuhan khusus yang unik dan berbeda dengan anak pada umumnya tentu menjadi tantangan tersendiri bagi guru anak berkebutuhan khusus dalam memberikan didikan dan pendampingan di sekolah. Penelitian ini bertujuan untuk mengenalkan strategi koping stres dapat menjadi sebuah solusi dalam mengatasi tekanan yang dihadapi oleh guru yang menangani anak berkebutuhan khusus melalui konseling kelompok. Partisipan penelitian pada penelitian ini adalah guru anak berkebutuhan khusus di Sekolah XX Surabaya. Penelitian ini merupakan penelitian kuasi eksperimental one-group pretest-posttest design yang menggunakan teknik analisis paired sample t-test untuk mengukur perbedaan tingkat stres sebelum dan sesudah diberikan intervensi kelompok dilakukan. Berdasarkan hasil analisis statistik, diketahui terdapat penurunan tingkat stres dari kategori berat menjadi ringan dan sedang secara signifikan, dengan nilai sig. (2-tailed) sebesar 0.008 (<0.05). Hasil penelitian secara kualitatif juga menunjukkan bahwa ketiga partisipan memperoleh efek terapeutik dari konseling kelompok yang dilakukan melalui proses refleksi, keterlibatan saat mengekspresikan emosi, mengidentifikasi masalah, memberi feedback, penemuan insight dari proses diskusi dan interaksi, mendapat validasi dan didengarkan, serta terbentuknya cara pandang dan perilaku baru yang lebih konstruktif dan adaptif dalam mengatasi stres. Maka, dapat disimpulkan bahwa konseling kelompok terkait coping stress strategy mampu menurunkan tingkat stres pada guru yang menangani anak berkebutuhan khusus di Sekolah XX Surabaya.